Investigating the role of WT1-expressing progenitors and the function of WT1 in visceral adipose tissue angiogenesis - Aldea, Teodora Valentina (The University of Edinburgh, 2021)
Unlike brown or subcutaneous white adipose tissue, visceral white adipose tissue (VWAT) is closely linked to cardiometabolic disease. The Wilms tumour 1 gene (WT1), an important developmental transcription factor, has been shown to be expressed in the progenitors of VWAT both in human and mouse. Moreover, adipose tissue expansion requires the formation of blood vessels and WT1 has previously been shown to be involved in angiogenesis during development and tumour formation. We were therefore interested in investigating the role of WT1 in VWAT angiogenesis by characterising the different WT1-expressing microvascular cell populations in VWAT and by focusing on the function of WT1 in angiogenesis. In order to look into the role of WT1 and WT1-expressing cells in vitro and in vivo, we used a lineage tracing (Wt1CreERT2; mTmG) mouse line and a reporter (Wt1GFP/+) line. Additionally, we used a conditional knock-out (CAGCreERT2; Wt1loxP/loxP) model, obtained by crossing CAGCreERT2 mice, where CreERT2 is expressed ubiquitously under the synthetic CAG promoter, with floxed Wt1loxP/loxP mice. We analysed WT1 expression in several main VWAT depots present in mice (epididymal, omental, mesenteric, perirenal and pericardial) and found that WT1 is expressed by CD31+ endothelial cells and PDGFRβ+ pericytes in several VWAT depots. Moreover, our lineage tracing experiments revealed that WT1-expressing cells give rise to cells which reside in the perivascular space of microvessels and that the contribution of WT1+ cells to the adipocyte population of VWAT is decreased in obesity. In humans, omental fat, which surrounds the intestines, is one of the most studied and easily accessible VWAT depots and our experiments on human omental VWAT showed that WT1-expressing cells are present in the perivascular area of microvessels and WT1 levels are increased during obesity. We further investigated the role of WT1, which we achieved by deleting WT1 in vitro in stromal vascular fraction cells and sorted pericytes. RNAi-mediated deletion of Wt1 did not show significant changes in in vitro angiogenic potential. Finally, we aimed to investigate the differences between WT1+ and WT1- pericytes in visceral adipose tissue, by using RNA sequencing to analyse the transcriptome of the two populations. Our data suggest that sub-populations of VWAT cells which express microvascular markers are derived from WT1-expressing cells, and also express WT1 in adulthood, which points to a potential role of WT1 in VWAT homeostasis and expansion. However, in our in vitro experiments, knocking down Wt1 in murine adipose-derived SVF cells and pericytes did not impair angiogenic potential.
Keywords: WT1-expressing progenitors; WT1; visceral adipose tissue angiogenesis; visceral white adipose tissue; cardiometabolic disease; Wilms tumour 1 gene; adipose tissue expansion; impair angiogenic potential